Análisis de la evaluación del desempeño laboral y su incidencia en el clima organizacional para el personal administrativo de la Unidad Educativa Quevedo, cantón Quevedo, año 2015 - Segovia Sánchez, Karen Soraya (2015)
The aim of this study was to analyze the performance appraisal and its impact on organizational climate for the administrative staff of the Education Unit Quevedo Canton. 2015, for which the following research methods are used: for tabulating statistical information obtained from surveys and interviews, and then present them as tables and graphs; qualitative applied to organize the data collected, transcribe to text, ie, documents, records, annotations, in the Quevedo Educational Unit , descriptive from the words of the people, spoken or written data; inductive was applied to obtain the primary information of public servants from Quevedo Education Unit Quevedo, so that was learned firsthand in performance level, organizational climate that has been created in the institution; deductive this method was applied to the analysis of the interviews conducted in the field of public servants, to determine the need that exists in terms of job performance and organizational climate. After processing all the information obtained, he reached the following conclusions: not all accept or acknowledge their mistakes when comment is governed by laws, regulations, institutional regulations and ministerial; not everyone agrees with the conditions under which they perform their activities. The human talent Quevedo Education Unit Quevedo feel proud to belong to this institution. Regarding the organizational climate supports improvement plans of the institution; It should be mentioned that not all participate in integration activities that are scheduled between peers and others with family; not all considered to be part of a team; exists in the personal sense of solidarity also can perform several activities at once. However, not everyone believes that an adequate organizational climate; evidenced weaknesses in both performance and organizational climate we proceed to make the proposal.